Nursing experience of corneal collagen cross-linking in treating keratoconus - WangFeipeng; TianBishan (眼科学报; 卷 30, 编号 3 (September 2015): 《眼科学报》, 2015)
Purpose: To summarize the nursing experience and clinical efficacy of corneal collagen cross-linking in treating keratoconus. Methods: Preoperative and postoperative nursing and medical record of 30 patients (31 eyes) undergoing corneal collagen cross-linking were retrospectively analyzed. Results: The the severity of diseases in all 30 patients (31 eyes) was properly controlled. All cases were fully recovered. The visual acuity at postoperative one month was improved in all cases. Conclusion: assistance in terms of preoperative examination, education of health knowledge and effective psychological nursing play a pivatol role in the nursing before and after corneal collagen cross-linking. Following surgery, postoperative changes in the the severity of diseases should be strictly observed. Much attention should be diverted to ease patients' pain, prevent infection and accelerate the healing of corneal epithelium.